ANALYSIS OF FINANCIAL DISTRESS AND BANKRUPTCY OF PT GARUDA INDONESIA TBK - Hadi Sucipto, Rakhmat; Daniel, Daniel; Sumantri, Fazhar; Indra, Natal (JURNAL EKBIS, 2024)
The research uses five bankruptcy prediction models, namely Altman, Springate, Grover, Zmijewski, and Ohlson. The research complements this with an independent samples t-test. The results of the analysis prove that the company is experiencing financial distress. Accuracy tests show that the Zmijewski method produces the highest accuracy rate of 80%, followed by Springate (60%), Grover (60%), Altman (50%), and Ohlson (40%). Based on the independent sample t-test, there are significant differences between the Altman and Springate, Altman and Zmijewski, Altman and Ohlson, Springate and Zmijewski, Springate and Ohlson, Grover and Zmijewski, and Grover and Ohlson methods, but there is no real difference between the Altman and Grover, Springate and Grover, and Zmijewski and Ohlson.